The Relationship Between Coping Style and School Adjustment Amongst Secondary School Students in Kisumu East Subcounty, Kenya - Winga Maureen Adhiambo; Agak John Odwar; Ayere A. Mildred (European Scientific Journal, ESJ, 2017)
The objectives of the study were to: establish gender differences in coping style; to establish differences amongst high and low achievers in their use of coping style and to determine the relationship between coping style and school adjustment. The study was guided, by Lazarus and Folkman’s Transactional theory, and Utretcht Work Engagement theory by Schaufeli and Bakker A descriptive survey research design was adopted for the study. The study population consisted of 4500 students. A sample size of 450 was selected using Stratified random sampling technique. Questionnaires and document analysis guide were used for data collection. Reliability was computed using Cronbach’s alpha and the results were as follows:- 0.6 for coping style 0.8 for school engagement and 0.7 for satisfaction with school. Content validity was ascertained in literature by the author. Data was analyzed using descriptive statistics as well as inferential statistics. It was found that there were no gender differences in coping style used. Low achievers reported more use of problem focused coping style. There were significant positive correlations between problem focused coping style and absorption as well as engagement. There were significant negative correlations between emotion focused coping and school adjustment among high achievers. The study may be useful to teachers, counselors, administrators and parents who will be able to assist students use appropriate coping styles.